Breast desmoid and Gardner syndrome - Piñeyro, Alberto; Perrier, José P.; Cartazzo, José M.; Castiglioni, Juan C.; Falconi, Luis (Cirugía del Uruguay, 1982)
A case of desmoid breast tumor in a patient with a Gardner's syndrome is presented. The rarity of this location is emphasized and a brief review of Gardner's disease is done.